THE FIRST APPLICATION OF ULTRA‑HIGH PERFORMANCE CONCRETE LINK SLAB IN MALAYSIA (ASEAN Engineering Journal, 2024)
Conventional expansion joints in road bridges often suffer from issues like leakage, debonded seals, concrete damage, and short service life. To address these problems, a solution involving flexible link slabs using normal strength concrete (NSC) was proposed. While this method can enhance serviceability and reduce maintenance costs, it lacks durability and tensile strength. Recent interest has focused on cast-in-situ ultra-high performance concrete (UHPC) link slabs due to their exceptional mechanical properties, early strength, durability, ductility, and energy-absorption capabilities. However, there is limited information on their field implementation. To address this gap, a pilot UHPC link slab was designed and implemented to replace a damaged bituminous plug expansion joint in a Malaysian road bridge. The pilot link slab followed New York State Department of Transport (NYSDOT) guidelines and used a high early strength UHPC mix with minimal shrinkage through the combination of expansive agents and shrinkage-reducing admixture (SRA). Monitoring the project over two years has shown no performance concerns with the UHPC link slab. This paper provides a comprehensive overview of the construction process, along with experimental results on the mechanical properties and shrinkage characteristics of the new UHPC.